THE EFFECT OF MOTIVATION AND LEARNING EFFECTIVENESS ON QUALITY OF GRADUATE STUDY PROGRAM PRIMARY TEACHER EDUCATION FKIP UNIVERSITY OF JAMBI - Yusdi Anra (Universitas Batanghari Jambi, 2018)
Abstract: This research was conducted to find out information and learning learning to the quality of study program S1 PGSD FKIP University of Jambi. This research uses survey method with correlational approach. The in place of this research is the study program S1 PGSD FKIP University of Jambi with the number of affordable population as much as 325 graduates. Data collection using questionnaire instrument. The sampling technique is done randomly with the following steps: First, calculate the target population of all PGSD S1 FKIP courses in Jambi University; second, the number of people reachable by lottery gives the order number; third, selecting 20 random people in statistics to try; Fourth, select 50 random people in the sample to sample the research. This research produces; (a) There are factors influencing the feasibility of PGSD S1 FKIP Universitas Jambi; (b) There are many things that affect the quality of graduates. The implication of this research is the effort to improve the quality that can be done by improving the motivation and study of the students of PGSD S1 FKIP Universitas Jambi.Keywords: Quality of graduates, motivation, effectiveness of learning